Prevalence of major neurological disorders in predominantly rural northwest India - Gandhi, Manoj K. (J Family Med Prim Care, 2020)
BACKGROUND: Epidemiological studies based on hospital population, geographic isolates, smaller population, and focused groups provide valuable information on the pattern of diseases, but do not reflect on the true prevalence rates or the changing trends of disease over a period of time in different communities. The present study was undertaken to determine the prevalence and pattern of various neurological disorders in Himachal Pradesh. METHODOLOGY: Study was carried out in urban and rural population of district Kangra of Himachal Pradesh. A proportional representation was given to each area in the allocation of sample size as per probability proportional to size (PPS) method using a two-phase design: 1) A screening phase and 2) a clinical evaluation phase. All subjects were screened and a subset (screen positive and 10% of screen negative) was identified for the detailed clinical evaluation after screening. A standardized screening battery (NIMHANS protocol) was used for this purpose. An individual was confirmed as a case of neurological disorder only after clinical evaluation. RESULTS: A total of 260 (out of 10,000 studied) individuals were found positive for neurological disorders yielding a crude prevalence of 2.6%. The crude prevalence for rural areas was found to be 2.28% (206/9000), whereas the crude prevalence in urban area was found to be 5.4% (54/1000). Migraine was the most common disorder. CONCLUSION: In view of the high crude prevalence of major neurological disorders, there is a need to develop capacity among healthcare professionals regarding them.